Two cases of Leukemoid reaction in premature infants caused by fetal inflammatory response syndrome - Meng-Ting Feng; Qiong Ji; Dan-Dan Liu; Wei Xu (BMC, 2024)
Abstract Background Fetal inflammatory response syndrome (FIRS) is a systemic inflammatory response caused by the activation of the fetal immune system. The serological diagnostic criterion for fetal inflammatory response syndrome is a cord blood interleukin-6 concentration that exceeds 11 pg/mL, while pathologic evidence indicates the presence of funisitis or chorionic vasculitis. It can affect all systems of the fetus. Alterations in patients' hematopoietic system are primarily reflected by changes in peripheral blood leukocyte and neutrophil counts. Case presentation We performed placental pathology to identify FIRS and showed two cases of neonatal leukemoid reaction caused by FIRS. These two babies' alterations in hematopoietic system resolves spontaneously with the inflammation relief, without specific interventions. During the 16‑month and14- month follow‑up period, their motor and intellectual development was normal. Conclusions . Neonatal leukemoid reaction is a reactive disease characterized by abnormal blood parameters similar to those of leukemia, but not leukemia. It is an aberrant hematopoietic response that typically resolves spontaneously with cause relief without requiring specific interventions.